Depression and the Diagnosis of MCI in a Culturally Diverse Sample in the United States. (12th November 2019) - Lang, Merike; Rosselli, Mónica; Greig, Maria T; Torres, Valeria L; Vélez-Uribe, Idaly; Arruda, Fernanda; Barker, Warren W; Garcia, Patricia; Loewenstein, David A; Curiel, Rosie E; Duara, Ranjan
Abstract: Objective: To analyze (1) whether there are ethnic differences in the severity of depressive symptoms between groups of elders classified as cognitively normal (CN) or amnestic mild cognitive impairment (aMCI) and (2) the influence of depressive symptoms on specific cognitive performance by ethnicity across diagnoses, controlling for covariates. Methods: 164 Hispanics residing in the United States (HAs) and European Americans (EAs) (100 women; M age = 72.1, SD = 8.0) were diagnosed as either CN or aMCI. Depressive symptoms were measured with the Geriatric Depression Scale (GDS-15). Cognition was assessed using the Loewenstein-Acevedo Scales for Semantic Interference and Learning (semantic memory), Multilingual Naming Test (confrontation naming), and the Stroop Test (Color–Word condition; executive function). A 2 × 2 univariate ANCOVA as well as linear and logistic regressions explored differences in depressive symptoms among diagnostic and ethnic groups. Results: Higher depression was seen in aMCI compared to the CN group for both ethnicities, after controlling for age, education, gender, and Mini-Mental State Examination score. Greater levels of depression also predicted lower scores in confrontation naming and semantic memory for only the EA group and marginally in scores of executive function for HA participants. GDS-15 scores of ≤ 4 also predicted less likelihood of aMCI diagnosis. Conclusions: Severity of depressive symptoms was associated with greater cognitive impairment, independent of ethnicity. Significant results suggest detrimental effects of depression on clinical diagnoses most evidently for subjects from the EA group.